Pengembangan Media Pembelajaran Berbasis Video pada Teori Pemesinan Frais - Fauzan, Muhammad Aziz; Rahdiyanta, Dwi (Jurnal Dinamika Vokasional Teknik Mesin, 2017)
This research is intended to produce a suitable video-based learning media on the making of helical gear in Milling Theory. This is a Research and Development type research incorporating six steps, namely: stating the potentials and problems, collecting data, designing the product, validation of the product design, revision of the design and product trials. Feasibility of the learning media was assesed by content-expert, media expert, teachers and students, by means of questionnaires. The quantitative research data were analized using quantitative-descriptive analysis technique. The product of this research is a learning media in the form of mp4 videos about Milling Machining practice. The media includes introductory music, videos, naration and animation. The feasibility level of the video-based learning media were assessed and presented in the form of percentages and classifications. The content-expert gave a feasibility level of 96.50% with classification of "very good", the media-expert gave 80.63% with classification of "very good", the teacher gave 76.25% with classification "very good" and the students’ responses reached 80.52% with classification of "strongly agree" to the use of the video-based learning media. It can be concluded that the video-based learning media of Milling Machining Theory is feasible to use in the teaching and learning process. Penelitian ini bertujuan untuk menghasilkan produk berupa media pembelajaran berbasis video pembuatan roda gigi heliks pada Teori Pemesinan Frais yang layak digunakan. Penelitian ini merupakan penelitian pengembangan dengan enam tahap, yaitu: potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi desain dan uji coba produk. Kelayakan media pembelajaran dinilai menggunakan angket oleh ahli materi, ahli media, guru pengampu dan siswa. Data penelitian berupa data kuantitatif yang dianalisis menggunakan teknik analisis deskriptif kuantitatif. Hasil penelitian berupa produk media pembelajaran Teknik Pemesinan Frais berbasis video berbentuk file mp4 yang dilengkapi dengan musik pengantar, video, narator dan animasi. Kelayakan media pembelajaran berbasis video dari ahli materi diperoleh persentase sebesar 96.50% dengan klasifikasi sangat baik, dari ahli media diperoleh persentase sebesar 80.63% dengan klasifikasi sangat baik, dari guru pengampu diperoleh persentase sebesar 76.25% dengan klasifikasi sangat baik dan berdasarkan respon penilaian siswa diperoleh persentase sebesar 80.52% dengan klasifikasi sangat setuju menggunakan media pembelajaran ini. Dengan demikian media pembelajaran berbasis video pada Teori Pemesinan Frais layak digunakan untuk proses pembelajaran.